Hippocampal dorsal CA1: Functional connectivity and role in HCN channelopathies in affective diseases and epilepsy - Tsz Wei So; Hoi Yi Choi; Haoyu Xu; Jinwei Zhu; Lei Shi; Jacque Pak Kan Ip (IBRO Neuroscience Reports)
The hippocampus is a complex structure consisting of the dentate gyrus (DG), cornu ammonis (CA) and the subiculum. CA1 is further subdivided into the ventral (vCA1) and dorsal (dCA1) compartments, with dCA1 believed to be crucial in spatial learning and memory as well as cognitive processing. Although dCA1 was traditionally thought to be not likely relevant to affective diseases, recent studies suggest otherwise. In fact, it has been found that diseases including certain types of post-traumatic stress disorder (PTSD), depression and epilepsy may be attributed to channelopathies in dCA1, particularly that of hyperpolarization-activated cyclic nucleotide gated (HCN) channels. However, it remains unclear how disruptions of HCN transcription, post-transcriptional modification and activation kinetics are related to changes of downstream structures along neural circuits. Their effect on behavioural changes and disease development, as well as the corresponding potential therapeutic strategies implicated in the findings have not been extensively studied as well. With the existing research gap and the significant clinical implications of dCA1 HCN channelopathies, the mechanisms of how defects of these channels result in brain disorders including PTSD, depression and temporal lobe epilepsy are worthy of further investigation. Therefore, in this review, we summarize the recent findings on the involvement of dCA1 HCN channelopathies in brain disorders after providing an outline on the neuroanatomy and functional connectivity of dCA1, and the features of HCN channels in that region. We also propose future directions of molecular and systems neuroscience studies, as well as the translational research on potential therapeutics that address the brain disorders related to dCA1 HCN channelopathies.